Antioxidant Activity Of Ginger (Zingiber Officinale) Oleoresin On The Profile Of Superoxide Dismutase (Sod) In The Kidney Of Rats Under Stress Condition - Tutik Wresdiyati; Made Astawan; Deddy Muchtadi; Yana Nurdiana (Jurnal Teknologi dan Industri Pangan, 2007)
Stress condition has beeb reported to decrease intracellular antioxidant-superoxide dismutase(SOD) in the liver and kidneyof rats. This study was conducted to evaluate the antioxidant activies of ginger oleoresin on the profile of superoxide dismutase(SOD) in the kidney of rats under stress condition. The stress condition was achieved by five days of fasting together with swimming for 5 min/day. Ginger oleoresin was orally administrated in a dose of 60 mg/KgBW/day for seven days. Drinking water was provided ad libitum to all groups. The treatment of ginger oleoresin significantly decreased malondialdehyde (MDA) levels and increased SOD activity, as well as immunohistochemicall, increased the content of copper, zinc-SOD (Cu, Zn-SOD) in the kidney tissues compared to that of untreated group. The antioxidant content in ginger oleoresin such as shogaol, zingeron, and gingerol, etc. were shownto have activities in the kidney tissues of rats under stress condition that is increasunf the profile of SOD. Ginger oleoresin treatment in combination both before and after stress gave the best result. Key words : antioxidant, ginger oleoresin, kidney, stress, superoxide dismutase (SOD)